Des “hermaphrodites de nationalité” ? Colonisation maritime en Algérie et naturalisation des marins-pêcheurs italiens de Bône (Annaba) des années 1860 à 1914 - Hugo Vermeren (Revue des Mondes Musulmans et de la Méditerranée)
The history of the maritime colonization of Algeria in the 19th century underlines the constant dialectic that the French colonial authorities were facing when dealing with the de facto Italian monopoly on fishing and sailing along the North African shores. Instrumental for the military conquest of Algeria, the Italian fishermen were considered essential not only for the fishing industry in this area but also for peopling port cities such as Bône. From the 1860s onwards, the official policy of pairing French sovereignty on land with the privilege of fishing in territorial waters aimed at naturalizing and settling these fishermen, but, in fact, it encouraged the trafficking of identity papers that would help them bypass rules that became more and more stringent. Accused of trading their naturalization for their support and their vote for local political leaders, these fishermen were at the center of the political crisis that affected Algeria at the end of the 19th century. From that moment, French authorities reconsidered the citizenship of the fisherman.